Association between choroidal pigmentation and posterior uveal melanoma in a white population. Issue 1 (23rd December 2003) - Harbour, J W; Brantley, M A; Hollingsworth, H; Gordon, M
Abstract : Background/aims: It is well known that light skin pigmentation is a risk factor for cutaneous melanoma. The aim of this study was to investigate the analogous association between choroidal pigmentation and posterior uveal melanoma. Methods: Cross sectional study of 65 consecutive patients diagnosed with posterior uveal melanoma (melanoma group) and 218 consecutive patients referred for general retinal evaluation (control group). All patients were white. A clinical grading system for estimating choroidal pigmentation was developed and histologically validated in seven patients. Results: Melanoma patients with light iris colour were significantly more likely to have darker choroidal pigmentation than controls (p = 0.005). Darker choroidal pigmentation was associated histologically with increased density of choroidal melanocytes (p = 0.005). Conclusions: Increased choroidal pigmentation, as a result of an increase in the density of pigmented choroidal melanocytes, is not protective but may actually be a risk factor for the development of posterior uveal melanoma in white patients. This finding may have implications for understanding the pathogenesis of uveal melanoma.